If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + 5) = 2 Reorder the terms: 2(5 + t) = 2 (5 * 2 + t * 2) = 2 (10 + 2t) = 2 Solving 10 + 2t = 2 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2t = 2 + -10 Combine like terms: 10 + -10 = 0 0 + 2t = 2 + -10 2t = 2 + -10 Combine like terms: 2 + -10 = -8 2t = -8 Divide each side by '2'. t = -4 Simplifying t = -4
| 12ab/a^2b^2/3b/2a | | 14-x+2x+5=180 | | h^2+18h+81=0 | | 16x(2)-8x=0 | | 3x+14=-31-6x | | 24=y-7y | | (-6x)(3)= | | 5y-4=3y-2 | | [x+8]-4=12 | | 3x+7=2x+5-8 | | 5+10x=-49+x | | 5+10x=-49x | | -8x-39+6x=-5 | | 11x+28=201 | | 3.3x-2.6y-9.1=0 | | 3x+5-sqrt(x^2-4x-8)=0 | | 25=x+(x-3)+(x+2) | | 72=2(11w-3)+2w | | 7z=5x+10 | | 3x^2-6x-40=0 | | 3x+5=sqrt(x^2-4x-8) | | 3x-106=14x+191 | | 5m+6=3 | | 0=2w^2+4w-16 | | 3(a-5)=a+1 | | 5x-9y=40 | | 9y^2-3y=1 | | 5x+74y= | | -2+2x=-8+10x | | (6a+5)=(5a+3) | | (3-y)*(3-y)+y^2=25 | | -3(x+6)-43=8-48 |